Impact of the Covid-19 Pandemic on the Digitalization of The EU Member States (UNWE Yearbook, 2023)
The new reality caused by the Covid-19 pandemic forced businesses to seek flexible solutions and the application of innovations in all fields of management. Living in the era of predictable unpredictability, the topic of entrepreneurship, digitalization, innovation, and competitiveness must be perceived by business representatives as a straw for existence. Thus, the main purpose of the current study is to identify good practices and innovative trends in the field of management and entrepreneurship utilizing digital solutions. The research object is the EU member states and it is focused on the e-commerce, web sale, and way of communication of the enterprises under the pandemic. For the evaluation of good practices and their possible implementation in business, we used comprehensive desk research based upon literature review and secondary analysis of empirical data in the period December 2021 – March 2022. Empirical data collected from national and international empirical studies conducted by private and state sociological agencies, as well as authors' teams of scientific and educational institutions, are the arrays on which secondary data processing was made. The results show that innovative management behavior of digital enterprises can provide added value based on the favorable reputation that they create.